BMS COLLABORATIVE LEARNING TO ANSWER THE CHALLENGES TOWARDS THE ENGLISH TEACHING AND LEARNING DURING THE PADEMIC OF COVID 19 VIRUS - Nina Khayatul Virdyna (The Ellite of Unira, 2021)
Corona virus has ruin all factors of life in the world. The most fact is in the education life. The students are suffer by the non-active school activity for some while. The teacher are suffer from the difficulties to bring the material to the students. The government has offer a lot of solutions. But some countries with some background of economic and geographical factors may suffer some problems. Here, the magic of a teacher, he has the authority to give the solving toward these problems. On these article the author offers three solution method of teaching and learning over the pandemic. The learning that the author offer is Blended learning, Mobile learning and STEAM learning. Those learnings will become the alternative solution for teaching English during the Pandemic. The collaboration of those will be use in one meeting or one session of English teaching and learning